Insights into the relationship between antimicrobial residues and bacterial populations in a hospital-urban wastewater treatment plant system - Ana Rita Varela (2014)
The relationship between antimicrobial residues, antibiotic resistance prevalence and bacterial community composition in hospital effluent and in the receiving wastewater treatment plant was studied. Samples from hospital effluent, raw inflow and final effluent of the receiving wastewater treatment plant were characterized for amoxicillin and ciprofloxacin resistance prevalence, content of heavy metals and antimicrobial residues and bacterial community structure, based on 165 rRNA gene PCR-DGGE analysis. The concentration of fluoroquinolones, arsenic and mercury was in general higher in hospital effluent than in raw inflow, while the opposite was observed for tetracyclines, sulfonamides and penicillin G. The prevalence of ciprofloxacin resistance was significantly higher in hospital effluent than in raw inflow. The concentration of antimicrobial residues was observed to be significantly correlated with the prevalence of antibiotic resistant bacteria and with variations in the bacterial community. Hospital effluent was confirmed as a relevant, although not unique, source of antimicrobial residues and antibiotic resistant bacteria to the wastewater treatment plant. Moreover, given the high loads of antibiotic residues and antibiotic resistant bacteria that may occur in hospital effluents, these wastewater habitats may represent useful models to study and predict the impact of antibiotic residues on bacterial communities.